Implementation of anti-corruption model as one of the major instruments in fighting corruption - Lilia Bakunchik; Olena Holota (Social Development & Security, 2019)
The article deals with historical aspects and international experience in developing anti-corruption models as well as describing the problems of implementation of such models in governmental establishments in Ukraine. Traditionally, corruption is the biggest problem for developing countries which is hard to fight. Fighting corruption in Ukraine has been presented in several comprehensive reviews. The reviews show us a list of concerns about serious changes in the field. Currently, there is an objective necessity to make more decisive steps to tackle corruption, which certainly is the important feature towards the improvement of the economic situation in the country. It should be noted that the implementation of anti-corruption models has been one of the most effective means of combating corruption for economically developed countries. In Ukraine, a course for implementing an anti-corruption model based on the creation of specialized anti-corruption bodies was chosen. However, there is the urgent need to mend a number of the legal and technical flaws of current legislation in order to guarantee the proper functioning of newly established state anti-corruption institutions.